Analysis of Gen Z Students' Perceptions of the Use of Digital Payment and Its Impact on Customer Satisfaction - Dellya Dievha Paramytha; Pradana Jati Kusuma; Ana Kadarningsih; Diana Puspitasari (International Journal Business, Management and Innovation Review, 2025)
This study aims to analyze the influence of perceived ease, trust, and benefits on the interest in using digital payments and their impact on customer satisfaction among Generation Z students. The focus of this study is to explore the relationship between these factors and how they affect digital transaction behavior and user satisfaction levels. Using a quantitative approach, data were collected from 185 Generation Z student respondents through purposive sampling techniques and distributed using questionnaires. The analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach using Smart PLS4 software. The results showed that perceived ease, trust, and benefits had a positive and significant effect on customer satisfaction. In addition, the use of digital payments also had a direct positive effect on satisfaction, but did not act as a mediating variable in the relationship between user perceptions and satisfaction. These findings indicate that perceptions of service quality have a greater influence on satisfaction than frequency of use. This study provides theoretical and practical contributions in understanding the behavior of digital payment users among Gen Z students.